Nonalloyed ohmic contact development with n+ InGaN regrowth method and analysis of its effect on AlGaN/GaN HEMT devices. (May 2023) - Toprak, A.; Özbay, E.
Abstract: In this study, the DC performance of AlGaN/GaN based HEMT devices of different geometries (designed to operate in the S, X and Ka-band frequency ranges) with regrown degenerately doped n + In0.12 GaN nonalloyed ohmic contacts on different epitaxial structures were investigated. Once the optimal recess etch depth and regrowth thickness for drain and source contacts were determined, the effects of alloyed and nonalloyed ohmic contacts on the maximum drain current (IDS, max ), ON‐resistance (Ron ), maximum DC transconductance (gm ), pinch-off voltage (Vth ), drain leakage current (ID, leak ), and gate leakage current (IG, leak ) were investigated for S, X and Ka-band HEMT devices. The results showed that the use of nonalloyed ohmic contacts resulted in decreasing Rc with a better surface morphology. Additionally, the nonalloyed ohmic contact structure with low contact resistance caused an increase in the IDS, max and gm values by reducing the Ron resistance, and also reducing the ID, leak and IG, leak leakage currents by preventing the surface distortions and trap formations due to the absence of high temperature. Although there was no dramatic change in Vth for S, X and Ka-band HEMT devices, Vth shifts towards positive in S and X-band devices, and towards negative in Ka-band devices.